Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas XI SMA Negeri 4 Sumatera Barat: Indonesia - Detia Fitri, Lika; Umar, Fahkrullah I Tama; Santi, Nirmala (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2024)
This research aims to determine the results of solving mathematics problems for class XI students at SMA Negeri 4 West Sumatra, whether using the jigsaw type cooperative learning model is better than conventional learning. The hypothesis in this research is that the jigsaw type cooperative learning model is better than conventional learning in class XI SMA Negeri 4 West Sumatra. This research is an experimental research with a randomized control group only design. The population in this study were all class XI students at SMA Negeri 4 West Sumatra, 36 students in the experimental class XI F3 and the control class The results of students' mathematical problem solving in the experimental class can be seen from the learning results of students' problem solving ability tests with an average of 69.95, better than those in the control class with an average of 61.72. Hypothesis testing using the t^' test was previously tested for normality with the value L_count<L_table (0.1169 < 0.1477) in the experimental class and (0.0984 < 0.1477) in the control class, meaning that both samples were normally distributed. For the homogeneity test, it was obtained that F_count>F_table (2.81 > 1.72) means that the sample class does not have a homogeneous variance. After carrying out the t^' test, it is obtained that -t_(α/2) < t^' < t_(α/2), namely -2.13479 < 1.63 < 2.13479 and 1.63 is in the acceptance area of ​​H_0. From these calculations it can be concluded that there is no significant difference in the jigsaw type cooperative learning model on the mathematical problem solving abilities of class XI students at SMA Negeri 4 West Sumatra.